Prospective Analysis of Economic and Social Development Through Special Economic Zones (SEZs): Pakistan a Case in Point - Iqbal, Muhammad Zafar; Ahmad, Bashir (iRASD Journal of Economics, 2024)
This paper seeks to link the concept of SEZs with social developments in developing countries like Pakistan. In the larger context of human developments, social and general wellbeing of the people is closely linked with the infrastructural enhancement, overall employment of human resource and economic growth in a country. Creation of SEZs is one of the mechanisms to enhance human hands’ engagement. SEZs create those environments which are growth centric in the most comprehensive manner. In the recent history of human developments, it has worked very well in China which raised living standards of the people in record times. The concept of SEZs is based on business facilitation at one place with minimum cost; yet attaining optimum proficiency. The paper is based on secondary data from the official circles of Pakistan and China as well as the literature review. The study follows a qualitative analysis of secondary data as available in publications and official websites. Since Pakistan was already part of Chinese Belt and Road Initiative (BRI), the idea of establishing CPEC (China Pakistan Economic Corridor) prompted to develop SEZs in synchronicity for boosting the economic growth. The study also allows comparative views of SEZs especially in developing countries to draw relevance to those envisaged in Pakistan. In synch with the developments centered around CPEC; in Pakistan, the SEZs have started coming on grounds in a phased process. The study concludes with outcomes like creating similar conditions as those of Chinese to have compatible and comparable success standards in Pakistan.